Hubungan Self Efficacy Akademik dengan Prokrastinasi Akademik pada Mahasiswa yang Sedang Menyelesaikan Skripsi - Annisa Rosni Zusya; Sari Zakiah Akmal (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
Having graduated not at the right time is a common phenomena among college students and procrastinantion which is delaying the final assignment become the reason. One of factors that affect procrastination is self-efficacy. Self-efficacy that is predicting academic achievement is academic self-efficacy. This research uses quantitative methods to examine the relationship between academic self-efficacy and academic procrastination among 210 students who are completing the last assignment. Instrument used are academic procrastination scale and academic self-efficacy scale. Result shows that there is no significant correlation between academic self-efficacy and academic procrastination among students who were completing the last assignment (r = -0.059, p = 0.398). Besides, academic procrastination had significant differences by age, gender, year of admission, residence, and activities. In the same time, the academic self-efficacy had differences by age, year in, obstacles and activities.